The Strategy of Strengthening Pancasila Ideology In The Digital Age - Oksep Adhayanto; Nazaki Nazaki; Nanik Rahmawati; Dewi Haryanti; Nurhasanah Suwardi; Rilo Pambudi (Fakultas Hukum Universitas Lampung, 2021)
This research attempts to analyze the implementation of the Pancasila ideology amid current digitalization. One of the markers of this digital era is the erosion of space and national boundaries for every citizen. Indonesia's large population can be a strength or weakness of the Pancasila ideology. For this reason, systematic steps are needed to make the values of Pancasila remain as a way of life for the Indonesian. This type of research is normative research that uses literature as a primary data source. The presentation of the data is conveyed by a qualitative descriptive method. The conclusion of this study is the need to strengthen Pancasila ideology in the digital era through efforts to reaffirm the fundamental values of Pancasila to society in general and the younger generation in particular. To ground the values of Pancasila, it is deemed necessary to involve millennial participation through digital influencer programs and the development of digital literacy based on Pancasila values and the doctrine of national values.